Changes in outpatient antibiotic prescribing for acute respiratory illnesses, 2011 to 2018. (17th December 2021) - King, Laura M.; Tsay, Sharon V.; Hicks, Lauri A.; Bizune, Destani; Hersh, Adam L.; Fleming-Dutra, Katherine
Abstract: Objectives: To describe acute respiratory illnesses (ARI) visits and antibiotic prescriptions in 2011 and 2018 across outpatient settings to evaluate progress in reducing unnecessary antibiotic prescribing for ARIs. Design: Cross-sectional study. Setting and patients: Outpatient medical and pharmacy claims captured in the IBM MarketScan commercial database, a national convenience sample of privately insured individuals aged <65 years. Methods: We calculated the annual number of ARI visits and visits with oral antibiotic prescriptions per 1, 000 enrollees overall and by age category, sex, and setting in 2011 and 2018. We compared these and calculated prevalence rate ratios (PRRs). We adapted existing tiered-diagnosis methodology for International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) codes. Results: In our study population, there were 829 ARI visits per 1, 000 enrollees in 2011 compared with 760 ARI visits per 1, 000 enrollees in 2018. In 2011, 39.3% of ARI visits were associated with ≥1 oral antibiotic prescription versus 36.2% in 2018. In 2018 compared with 2011, overall ARI visits decreased 8% (PRR, 0.92; 99.99% confidence interval [CI], 0.92–0.92), whereas visits with antibiotic prescriptions decreased 16% (PRR, 0.84; 99.99% CI, 0.84–0.85). Visits for antibiotic-inappropriate ARIs decreased by 9% (PRR, 0.91; 99.99% CI, 0.91–0.92), and visits with antibiotic prescriptions for these conditions decreased by 32% (PRR, 0.68; 99.99% CI, 0.67–0.68) from 2011 to 2018. Conclusions: Both the rate of antibiotic prescriptions per 1, 000 enrollees and the percentage of visits with antibiotic prescriptions decreased modestly from 2011 to 2018 in our study population. These decreases were greatest for antibiotic-inappropriate ARIs; however, additional reductions in inappropriate antibiotic prescribing are needed.